2012
DOI: 10.11130/jei.2012.27.1.167
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Policy and Asset Price Interactions in India: Should Financial Stability Concerns from Asset Prices be Addressed Through Monetary Policy?

Abstract: The dynamic interactions between monetary policy and asset prices have conventionally been examined in terms of the asset price channel of transmission of monetary policy, given the pre-crisis analytical consensus against the use of monetary policy to respond directly to asset price inflation. In the post sub-prime crisis period, however, there has been an overwhelming intellectual support for revisiting the issue of whether monetary policy should become more sensitive to asset price trends and respond proacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
1
4
1
Order By: Relevance
“…This study did not find evidence for mediating role of stock prices or the transmission mechanism of monetary policy involving asset prices, unlike studies of Mishkin (2001), and Singh and Pattanaik (2012). Since monetary policy can also be transmitted through other channels, except those involving asset prices, future studies can be directed towards testing for existence of credit and interest channels of monetary transmission, in Nepali context.…”
Section: Implications and Future Research Directionscontrasting
confidence: 66%
See 1 more Smart Citation
“…This study did not find evidence for mediating role of stock prices or the transmission mechanism of monetary policy involving asset prices, unlike studies of Mishkin (2001), and Singh and Pattanaik (2012). Since monetary policy can also be transmitted through other channels, except those involving asset prices, future studies can be directed towards testing for existence of credit and interest channels of monetary transmission, in Nepali context.…”
Section: Implications and Future Research Directionscontrasting
confidence: 66%
“…This showed that monetary policy authorities in Nepal took into account the development in stock market while devising monetary policy, which was also in accordance with their mandate to maintain financial stability -stipulated as an objective in Nepal Rastra Bank Act, 2002. Findings also suggested that asset prices did not mediate the relationship between monetary policy variables and monetary policy goals. This showed that monetary policy transmission through asset prices was weak or non-existent in the context of Nepal, unlike in Mishkin (2001), and Singh and Pattanaik (2012). The reason for such insignificant mediating role of asset prices might be due to typical features of Nepali economy viz., small, underdeveloped, frictions in credit market, very few financial instruments, domination of banks in financial system, profound dependency on a single country, fixed exchange rate regime, and so forth.…”
Section: Monetary Policy and Stock Price 25mentioning
confidence: 97%
“…This finding is enough to get attention when other studies prove that there is no asset price channel effect on monetary transmission. One of the results of research conducted by Singh (2012) shows that changes in asset prices do not affect the inflation path. However, the transmission of asset price channel in the future will be very important for any central bank because it is a monetary policy transmission channel related to the market value of assets and individual wealth as important variables.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Shibuya (1992) claims that as long as CPI and GDP deflator are stable, asset price inflation should not be taken as dangerous. On the other hand, Singh and Pattanaik (2012) suggest that consumer price index is not a healthy indicator of inflation trends as asset price inflation, and monetary authority should avoid credit bubbles and excess liquidity conditions, in order to prevent asset price bubbles. What both sides fail to take into account is the side effect on wealth distribution.…”
Section: Discussionmentioning
confidence: 99%